Calibration Concepts of Multi-Channel Spaceborne SAR - Rommel, Tobias; De Almeida, Felipe Queiroz; Huber, Sigurd; Jaeger, Marc; Krieger, Gerhard; Laux, Christopher; Martone, Michele; Villano, Michelangelo; Wollstadt, Steffen; Younis, Marwan (CEOS SAR Workshop on Calibration and Validation (CEOS SAR CalVal), 2016)
Future synthetic aperture radar (SAR) systems will incorporate multi-channel Digital Beam-Forming (DBF) capabilities and operate in new modes. These SAR instruments offer new opportunities but also challenges for calibration. For example on-board real time channel adjustment is unavoidable, but then the on-board digital signal processing capabilities are also readily available in DBF SAR. In any case, current instrument calibration concepts can not be extrapolated to future multi-channel SAR. Thus a new approach is requires required here. This paper reviews the calibration functionality of state-of-the-art spaceborne SAR and then suggest a calibration concept for future SAR.
DLR Import::2019-04-03